Quality of yogurt supplemented with whey protein concentrate and effects of whey protein denaturation - Landge, Virendra Laxman (Kansas State University, 2009)
Yogurt is a good source of whey proteins, which have been reported to provide positive health benefits. During yogurt manufacture, the yogurt mix receives a heat treatment which pasteurizes the product, denatures the whey proteins affecting their availability, and enhances quality attributes. Thus the objective of this research was to improve the undenatured whey protein content in yogurt. The study was divided in two parts. The first part focused on the effect of pasteurization treatments of yogurt mixes (65 °C for 30 min vs. 90 °C for 10 min) on the yogurt firmness, G’, L*, syneresis and water holding capacity (WHC), and how these properties change as a function of storage. Nonfat dry milk (NFDM) was reconstituted (~11% w/v) pasteurized, cooled, inoculated with yogurt culture, incubated to pH 4.5, stored at 5 °C ±1 and evaluated for various physical and chemical properties on days 1, 15 and 29. The experiment was replicated 3 times and data were analyzed by SAS®. Yogurt samples had a 5-fold difference in whey protein denaturation (WPD) and the greater the WPD the greater the firmness, G’, L* and WHC but lesser the syneresis. During yogurt storage, L*, G’, syneresis and WHC increased. The second part of this research focused on whey protein concentrate (WPC) addition (3%) in yogurt mix combined with two pasteurization treatments (70 °C for 30 min vs. 90 °C for 10 min) to determine their effects on the yogurt quality. Yogurt mixes were formulated using 12.5% NFDM or 9.5% NFDM and 3% WPC and a procedure similar to the previous study was followed. The WPC addition resulted in a yogurt with decreased firmness, G’, WHC but increased syneresis. Yogurt made from mixes pasteurized at 90 °C for 10 min had ~60% WPD and comparable quality attributes regardless of WPC addition. Thus, additional WPC and less WPD in this study resulted in a yogurt with slightly lesser quality attributes but more undenatured whey proteins in the final yogurt.
Keywords: Set yogurt; Whey Protein; Whey protein denaturation; Texture; Syneresis; Water holding capacity; Agriculture, Food Science and Technology (0359)